A social enterprise business model for social entrepreneurs: theoretical foundations and model development. (2015) - Lee, In
Social enterprise is drawing increased attention from the entrepreneurship and marketing area. While there have been a significant number of studies in the management and operational side of social enterprise, no overarching theoretical framework of the business model exists for social enterprise. The current theoretical framework of the business model in the strategic management area does not adequately take into consideration the unique characteristics of social enterprise and the context within which they must operate. By applying theoretical foundations in the strategic management, this paper fills the current research gap and develops a social enterprise business model. Finally, management guidelines of the social enterprise business model are discussed for social entrepreneurs.